A holistic quality taxonomy for virtual reality experiences - Hameed, Asim; Möller, Sebastian; Perkis, Andrew (Frontiers in Virtual Reality, 2024)
The rapid advancement of virtual reality (VR) technology has brought many immersive experiences, each designed to transport users into captivating virtual worlds. While these experiences aim to provide a sense of presence and engagement, the factors contributing to a truly immersive experience are often complex and multifaceted. Existing scholarship has predominantly focused on specific aspects of user experience, such as psychological factors (e.g., sense of presence), emotional factors (e.g., enjoyment), or design-related factors (e.g., interface usability). This fragmented approach has impeded a comprehensive understanding of the overall quality of VR experiences. To address this, we propose a multidimensional taxonomy encompassing five essential qualities: immersivity, interactivity, explorability, plausibility, and believability. The framework aims to disentangle the complex, interrelated facets shaping VR experiences for a more systematic evaluation. Immersivity refers to the subjective sense of presence and "being there" in a virtual environment. Interactivity denotes the ability to interact with virtual objects, promoting engagement dynamically. Explorability refers to users' freedom to navigate and discover new elements. Plausibility examines the logical congruence of the virtual environment's rules and behaviors. Finally, believability relates to the world-building and internal coherence of the VR world. This taxonomy provides a structured approach to look at VR experiences holistically, assessing the interplay of these facets to facilitate a more objective, comprehensive evaluation, capturing the multidimensional nature of VR experiences. In summary, our proposed taxonomy marks an essential step toward systematic VR evaluation, providing guidance for researchers and highlighting factors integral to VR quality.